Differences in nucleotide excision repair capacity between newly diagnosed colorectal cancer patients and healthy controls - Slyskova, Jana; Naccarati, Alessio; Pardini, Barbara; Polakova, Veronika; Vodickova, Ludmila; Smerhovsky, Zdenek; Levy, Miroslav; Lipska, Ludmila; Liska, Vaclav; Vodicka, Pavel (Mutagenesis, 2012)
Alteration of DNA integrity is a potential cause of cancer and it is assumed that reduced DNA repair capacity and accumulation of DNA damage may represent intermediate markers in carcinogenesis. In this case-control study, DNA damage and nucleotide excision repair capacity (NER-DRC) were assessed in association with sporadic colorectal cancer (CRC). Both parameters were quantified by comet assay in blood cells of 70 untreated incident patients and 70 age-matched healthy controls. mRNA expression and polymorphisms in relevant NER genes were concurrently analyzed. The aim of this study was to characterize incident CRC patients for NER-DRC and to clarify possible relations between investigated variables. Comet assay and mRNA expression analysis showed that CRC patients differ in repair capacity as compared to controls. Patients had a lower NER-DRC and simultaneously they exhibited higher endogenous DNA damage (for both P < 0.001). Accumulation of DNA damage and decreasing NER-DRC behaved as independent modulating parameters strongly associated with CRC. Expression levels of 6 out of 9 studied genes differed between groups (P ≤ 0.001), but none of them was related to DRC or to any of the studied NER polymorphisms. However, in patients only, XPC Ala499Val modulated expression levels of XPC, XPB and XPD gene, whereas XPC Lys939Gln was associated with XPA expression level in controls (for all P < 0.05). This study provides evidence on altered DRC and DNA damage levels in sporadic CRC and proposes the relevance of the NER pathway in this malignancy. Further, alterations in a complex multigene process like DNA repair may be better characterized by functional quantification of repair capacity than by quantification of individual genes transcripts or gene variants alone.
Keywords: senioři; messenger RNA; DNA Damage; DNA-Binding Proteins; Real-Time Polymerase Chain Reaction; celogenomová asociační studie; senioři nad 80 let; genotyp; Male; kolorektální nádory; Comet Assay; Prognosis; Genotype; poškození DNA; Middle Aged; Colorectal Neoplasms; mužské pohlaví; studie případů a kontrol; Adult; polymorfismus genetický; kvantitativní polymerázová řetězová reakce; Aged, 80 and over; Polymorphism, Genetic; ženské pohlaví; prognóza; RNA, Messenger; Humans; oprava DNA; lidé středního věku; kometový test; DNA vazebné proteiny; dospělí; DNA Repair; Female; Aged; Genome-Wide Association Study; lidé; Case-Control Studies